Determinants of spatial weights in spatial wage equations: A sensitivity analysis - Gabriel M. Ahlfeldt; Arne Feddersen (University of Hamburg, Faculty of Business, Economics and Social Sciences, Chair for Economic Policy, 2008)
Recent empirical tests for a spatial wage structure have confirmed regional accessibility to be a significant determinant for income, although estimates vary considerably with respect to the geographic scope of estimated demand linkages. Our study is the first to estimate spatial demand linkages for a set of more than 1,300 European NUTS 3 regions (U.S. county equivalent) based on effective road travel times. We conduct a series of more than 200 estimations on the basis of the Harris Market Potential Equation in order to evaluate the estimates' sensitivity to various model alterations in a meta-analysis. In line with the distinct spatial interactions captured at different levels of aggregation, our estimates reveal lower average travel costs when data aggregated to larger geographic units are used. The largest sensitivity, however, is found for sample restrictions to a limited geographic coverage, which is likely to account for the inconsistent results available in the literature.
Keywords: F15; R12; 330; Market Potential; Nominal Wage Equation; New Economic Geography; Sensitivity Analysis